Jump Start State of the art report march 2021 (Canadian Tire Jumpstart Charities, 2021)
Sport has the power to unite communities and the nation - the spark we`ll need more than ever post-pandemic. In its absence, the importance of sport and play has become more apparent than ever. But with ongoing stoppages, the organizations that Canadian kids rely on are more at risk than ever before.